LEGAL ASPECTS OF IRON ORE PROCESSING IN THE KRYVYI RIH IRON ORE BASIN - Mikhailov, V.; Shniukov, S.; Kostruba, A.; Kharytonova, T.; Hryhorieva, K.; Tkalych, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The current version of the Tax Code allows for misinterpretation of the interpretation of the term "primary processing of mineral resources". In particular, the tax authorities believe that the primary processing of mineral raw materials includes magnetite concentrate, which in this case is subject to taxation. That is, a number of mining and processing enterprises have faced the problem of double taxation, which threatens significant financial losses. Accordingly, this led to the choice of topic for writing this article, the purpose of which is to conduct research on changes in mineral forms of minerals (iron ore), their aggregate-phase state, crystal chemical structure during production processes at mining, crushing and concentrating production of Kryvyi Rih mining and processing enterprises, and establishing at what stage of production the primary processing of minerals for the purposes of rent taxation is completed and whether the position of enterprises on limiting primary processing by the stage of fragmentation meets the requirements of the Tax Code of Ukraine.
Keywords: Tax code; subsoil use; double taxation; mineral resources; iron ore basin